Population Dynamics of Lake Whitefish, Coregonus clupeaformis, in Lake Michigan East of Door County, Wisconsin - Humphreys, James D. (University of Wisconsin-Stevens Point, College of Natural Resources, 1978)
Fish were tagged (2559 in 1975 and 2563 in 1976), and commercial catches were sampled to determine the vital statistics of and to fit predictive models to the lake whitefish population and fishery from the North and Moonlight Bay area (NMB) of Lake Michigan. Back-calculated lengths indicated that lake whitefish from NMB were recruited to the fishery during age 3+ (432 mm), and back-calculated lengths from NMB lake whitefish were similar to such lengths back-calculated from lake whitefish in other areas of Lake Michigan. The length-weight relationship exponent was 3.6 for Fall 1976 and Spring 1977 samples; no decrease in the exponent value was observed from the Fall to the Spring sample, and the NMB exponent was similar to that found for Europe Bay lake whitefish in 1948. Instantaneous growth rates (G) varied from 1.1 to 0.1 for ages 2 through 9, and 1.4 through 0.06 for ages 1 through 10 for the Fall 1976 and Spring 1977 samples, respectively; the growth rates were not statistically different for the two samples. The 1972-year class supported the NMB lake whitefish fishery in 1975, 1976, and 1977 by contributing 66 to 72% by number and 48 to 80% by weight to the harvest. Tagged lake whitefish moved extensively, but the primary area of recapture was NMB. When corrected for tag loss and non-response, an estimated 789 tags were recaptured in the first year of availability for the 1976 tags, yielding an exploitation rate estimate of 38%. Population estimates for NMB spawning stock (1.1 million) and the Wisconsin Lake Michigan population (1.2 to 1.5 million) indicated that the NMB spawning stock was a major component of the Wisconsin Lake Michigan lake whitefish population; the Wisconsin Lake Michigan fishery may be managed. as one stock. Total instantaneous mortality (Z) was 1.1, of which 0.63 was fishing mortality (F) and 0.47 was natural mortality (M). Ricker equilibrium yield and Beverton-Holt yield model calculations predicted yields within 86% of one another for the fishery in NMB at the 1976 level of fishing mortality. The Beverton-Holt model indicated that yield could be increased slightly but at the expense of catch per effort. The Ricker yield model predicted maximum yield at the 432-mm size limit; however maximum production was predicted at the 508-mm size limit if there were no change in natural mortality or growth. Production exceeded yield at the four size limits simulated (432,457, 483, and 508 mm). Data did not indicate that the 432-mm size limit should be changed. Critical size indicated that more fish should be harvested at a smaller size to obtain maximum yield, as 82% of the harvest was larger than the critical size of 489 mm.